2015
DOI: 10.1186/s13104-015-1175-z
|View full text |Cite|
|
Sign up to set email alerts
|

Outcome and prognosis of hypoxic brain damage patients undergoing neurological early rehabilitation

Abstract: BackgroundThe prevalence of patients suffering from hypoxic brain damage is increasing. Long-term outcome data and prognostic factors for either poor or good outcome are lacking.MethodsThis retrospective study included 93 patients with hypoxic brain damage undergoing neurological early rehabilitation [length of stay: 108.5 (81.9) days]. Clinical data, validated outcome scales (e.g. Barthel Index—BI, Early Rehabilitation Index—ERI, Glasgow Coma Scale—GCS, Coma Remission Scale—CRS), neuroimaging data, electroenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
47
1
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 25 publications
8
47
1
13
Order By: Relevance
“…This finding may be explained by similar acute care GCS scores between these 2 groups of patients. This is supported by a previous study by Heinz et al, who confirmed the significant associations of GCS score with functional recovery at discharge in patients with acquired brain injury [39].…”
Section: Discussionsupporting
confidence: 86%
“…This finding may be explained by similar acute care GCS scores between these 2 groups of patients. This is supported by a previous study by Heinz et al, who confirmed the significant associations of GCS score with functional recovery at discharge in patients with acquired brain injury [39].…”
Section: Discussionsupporting
confidence: 86%
“…In our study, the COPD patients did not demonstrate a significant different GM or WM volume when compared to normal controls. In our opinion, severe hypoxemia will finally lead to brain atrophy as reflected by the chronic phase of hypoxic‐ischemic brain injury (Heinz & Rollnik, ; Weiss, Galanaud, Carpentier, Naccache, & Puybasset, ), while brain atrophy may not be prevalent in the stable COPD patients. Meanwhile, a rigid multiple comparison correction method adopted in our statistical tests may also account for the negative result (Eklund, Nichols, & Knutsson, ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with severe TBI experience neurological problems, such as coma, which lead to Central nervous system (CNS) dysfunction . When the CNS becomes totally or almost totally impaired, comatose patients manifest loss or near‐loss of cognitive, physical and psychosocial functions . Therefore, one of the primary goals of rehabilitation professionals is to arouse patients from coma.…”
Section: Introductionmentioning
confidence: 99%